CONFINED FLUIDS AND THEIR ROLE IN PRESSURE SOLUTION - Anzalone A.; Young K.; Alcantar N.; Greene G.; Israelachvili J.; Boles J. (My University, 2006)
The process of pressure solution is defined as the dissolution of materials under high stress at grain-to-grain contacts and precipitation at interfaces under low stress. The kinetics of this process are still poorly understood mainly because of the large timescales involved. In this research, the Surface Forces Apparatus (SFA) technique was coupled with an optical interference technique for in situ visualization of the nanoscale deformations and thickness changes. The SFA was used to measure the forces (or pressures) and distances between two solid surfaces pressed together with a thin film between them. Using the SFA, combined with geological observations, we are studying the short-range colloidal forces between surfaces of mica and silica at the nanoscale such as van der Waals, electrostatic, and hydration forces. This study involves two cases, the symmetric case of mica in contact with mica and the asymmetric case of a quartz surface in contact with mica. Our results reveal highly subtle effects depending on the nature and concentration of the counterions present in the solution either of Na+, Ca2+, or mixtures of these ions, as well as on the pH. For the symmetric case, the equilibrium interactions of force F or pressure P versus fluid film thickness T have been measured between the mica surfaces across aqueous films in the thickness range from T = 25 Å down to contact separations around T = 0 Å, and depend on the solution conditions and applied lithostatic pressure. Measurements have also been made of the rates of diffusion of ions through such ultra-thin films and on the precipitation and growth of ionic crystallite layers on the surfaces. Our results show that the diffusion coefficient of hydrated sodium is two orders of magnitude lower than the diffusion of water into mica-mica cleavage and a factor of 40 lower than the coefficient of sodium ions in bulk water. For the asymmetric case, the dissolution of the quartz surface was observed to be dependent on the interfacial fluid composition and pH, the externally applied 'lithostatic' pressure, and the type of crystalline structure exposed to the mica surface. Our experiments also show that there is an initial stage after fresh solution is added in which the spacing between the surfaces increases, however, the thickness started decreasing steadily after approximately 4 h of exposure independently of the crystallinity of the quartz surface. For a particular set of conditions, the process eventually slows down and reaches equilibrium after some time, but a further increase in pressure restarts the dissolution process. This is also true for the addition of fresh interfacial solution during the experiment after a period of thickness fluctuation. These results are consistent with the observation that pressure solution of quartz is greatly enhanced with the presence of mica. © 2006 Elsevier B.V. All rights reserved.